Tools and institutions of interregional convergence: the case of Russian federal policy - Prof. Alexander Granberg; Alexander Pelyasov (European Regional Science Association (ERSA), 2002)
After a decade of reform contrasts between regions in Russia in per resident regional gross product and per resident real income have increased essentially. The challenge to smooth these inequalities is one of the high priorities for the contemporary Russian federal regional policy. For this purpose in the year 2001 federal program of diminishing interregional disparities was elaborated. In 2002 forty regions will receive federal assistance in this Program. Institutional factors on the regional level are critical to make this assistance more efficient. To understand this influence special research of the link between the structure of the regional authorities and the regional economic growth has been undertaken for 10 regions. The model of regional authority-'open corporation' is more effective in attracting additional external investments for the federal assistance money. The model of regional authority-'closed partnership' is more effective in decreasing transaction costs of utilising federal money in social projects to fight inequalities. In the ethnic republics federal assistance sometimes in reality can increase disparities as it is chanelled for the clan in power and not distributed evenly among all the groups and localities. The paper concludes by suggestion for the improvement of the contemporary federal regional policy in Russia.
Keywords: 330